Kriteria Pemilihan Metode Mengajar dalam Kegiatan Pembelajaran - Hasibuan, Nasruddin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2013)
In some schools, teachers do not apply suitable teaching media. Therefore, every time they teach the media and methods used remain the same without regarding the topics and materials. According to the Law of National Education System 2003 education is conscious effort to develop learners’ potential to make them religious, intelligent, and have good attitude and skill needed to develop self, society, and nation. This implies that to achieve the goal as mandated by the Law, the teachers implement good teaching method, materials, and media.